Effect of Capital Structure on the Performance of Deposit Money Banks - Ibrahim Sadiq, Abdulrashid; Kachollom, Pofi Wendy; Dasuki, Saminu Inuwa; Yusuf, Mohammad (International Journal of Accounting & Finance Review, 2017)
The objective of this study is to examine the effect of capital structure onthe financial performance of Deposit Money Banks in Nigeria. Secondary data was obtained from the financial statements of Deposit Money Banks listed in the Nigerian Stock Exchange.Four banks were selected as samples and data from their financial statements for a period of 10 years (2006-2015). The study has employed the use of Pearson correlation coefficient and GLS regression model to analyze the effect of capital structure on the performance of some selected. The performance variables used in the study were, Return on Asset (ROA), Return on Equity (ROE) and Return on Capital Employed (ROCE). Findings from the study showed that capital structure has an effect on the financial performance of listed deposit money banks in Nigeria.Based on the results, the study recommends thatdeposit money banks in Nigeria should employ an appropriate mix of debt and equity capital and strike a balance between their choice of capital structure and its effect on their performance, as this will affect the shareholders risk returns and the cost of capital. Furthermore, the banks should increase their assets as this will help them to be more positioned for better performance and the government should improve liquidity in the Nigerian Financial Market to enable deposit money banks raise long term debt and reduce over dependency on short term debt.